A Family of Superhelicenes: Easily Tunable, Chiral Nanographenes by Merging Helicity with Planar π Systems. Issue 33 (9th July 2021) - Reger, David; Haines, Philipp; Amsharov, Konstantin Y.; Schmidt, Julia A.; Ullrich, Tobias; Bönisch, Simon; Hampel, Frank; Görling, Andreas; Nelson, Jenny; Jelfs, Kim E.; Guldi, Dirk M.; Jux, Norbert
Abstract: We designed a straightforward synthetic route towards a full‐fledged family of π‐extended helicenes: superhelicenes. They have two hexa‐peri‐hexabenzocoronenes (HBCs) in common that are connected via a central five‐membered ring. By means of structurally altering this 5‐membered ring, we realized a versatile library of molecular building blocks. Not only the superhelicene structure, but also their features are tuned with ease. In‐depth physico‐chemical characterizations served as a proof of concept thereof. The superhelicene enantiomers were separated, their circular dichroism was measured in preliminary studies and concluded with an enantiomeric assignment. Our work was rounded‐off by crystal structure analyses. Mixed stacks of M‐ and P‐isomers led to twisted molecular wires. Using such stacks, charge‐carrier mobilities were calculated, giving reason to expect outstanding hole transporting properties. Abstract : We present the synthesis and in‐depth physico‐chemical characterization of a family of π‐extended helicenes that consist of HBCs fused via different five‐membered rings. Despite being only a small part of the compounds, the nature of the five‐membered rings has a huge impact on the properties of the whole molecule. We show the enantiomeric separation and circular dichroism properties together with X‐ray analysis and charge transport calculations.